Clinicopathological and molecular differences between right-sided and left-sided colorectal cancer in Japanese patients. (15th May 2018) - Natsume, Soichiro; Yamaguchi, Tatsuro; Takao, Misato; Iijima, Takeru; Wakaume, Rika; Takahashi, Keiichi; Matsumoto, Hiroshi; Nakano, Daisuke; Horiguchi, Shin-ichiro; Koizumi, Koichi; Miyaki, Michiko
Abstract : Comparing RCC with LCRC, elderly patients, female, advanced diseases, MSI, KRAS mutation, BRAF mutation and CIMP+ were significantly more frequent in RCC, whereas 18qLOH was significantly more frequent in LCRC. Abstract: Background: The aim of this study was to clarify clinicopathological features, frequencies of molecular biomarkers, and prognoses in Japanese colorectal cancer patients and compare them with right-sided colon cancer (RCC) and left-sided colorectal cancer (LCRC). Methods: We consecutively selected 575 colorectal cancer patients who underwent surgical resection from 2008 to 2011. RCC was located from the cecum to the transverse colon, and LCRC was located from the splenic flexure to the rectum. Frequencies of KRAS gene mutation, BRAF gene mutation, microsatellite instability (MSI), l18qLOH and CpG island methylator phenotype (CIMP) were statistically analyzed between groups. Results: Tumors were located in the RCC in 26.3% of patients and in the LCRC in 73.7%. Elderly patients, females and advanced diseases were significantly more frequent in the RCC group than in the LCRC group. However, venous invasion was significantly more frequent in LCRC than in RCC. Between groups, BRAF mutant type, KRAS mutant type, MSI and CIMP+ were significantly more frequent in RCC, whereas 18qLOH was significantly more frequent in LCRC. In overall survival, RCC demonstrated poor prognosis compared with LCRC; however, age, gender, stage, lymphatic invasion, KRAS status and BRAF status rather than tumor location were independent prognostic factors. In addition, the independent prognostic factors in RCC were different from those in LCRC in each stage. However, the consistency between OS and DFS was not observed in this study, excluding lymphatic invasion in LCRC. Conclusion: Comparing RCC with LCRC, RCC is different from LCRC in clinicopathological features, molecular biomarkers and prognostic factors in Japanese colorectal cancer patients. Since the proportions of molecular biomarkers of CRC in this study are different from Western CRCs, further studies are required to clarify the clinicopathological differences between Japanese CRCs and Western CRCs.